2014
DOI: 10.1002/lary.24934
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound to differentiate thyroglossal duct cysts and dermoid cysts in children

Abstract: It may be possible to differentiate between TGDC and midline DC preoperatively using ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 19 publications
2
22
0
1
Order By: Relevance
“…Oyewumi et al published ultrasound findings that more likely identified a TGDC than DC. The seven identifying features are internal septae, irregular cyst wall, ill‐defined margin, solid components, smaller distance from the base of the tongue, the presence of a tract, and intralesional Doppler flow . Each finding is scored as 0 or 1, and a total score ≥ 2 is highly suggestive of TGDC …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oyewumi et al published ultrasound findings that more likely identified a TGDC than DC. The seven identifying features are internal septae, irregular cyst wall, ill‐defined margin, solid components, smaller distance from the base of the tongue, the presence of a tract, and intralesional Doppler flow . Each finding is scored as 0 or 1, and a total score ≥ 2 is highly suggestive of TGDC …”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound confirmed the lesions to be well defined, homogenous, and hypoechoic cystic lesions ( Figure 1C Each finding is scored as 0 or 1, and a total score ≥ 2 is highly suggestive of TGDC. 4 Midline anterior neck inclusion cyst clinically resembles a giant milium in the midline anterior neck. This superficial location differentiates it clinically from DC.…”
Section: A S Ementioning
confidence: 99%
“…A thyroglossal duct cyst is usually hypoechoic, homogeneous, and well circumscribed on 2D US but may contain internal material of low echogenicity due to proteinaceous fluid secreted by the epithelial lining, internal hemorrhage, or cellular debris (Figure A). It may also have septa, irregular walls, and solid components . Preoperative imaging is performed to precisely locate it anatomically, to look for ectopic thyroid tissue, and to visualize possible evidence of malignancy .…”
Section: Techniquementioning
confidence: 99%
“…It may also have septa, irregular walls, and solid components. 30 Preoperative imaging is performed to precisely locate it anatomically, to look for ectopic thyroid tissue, and to visualize possible evidence of malignancy. 28 Solid mural components may predict malignant degeneration of the epithelial lining, which can occur in up to 1% of patients, most typically, a papillary carcinoma.…”
Section: Thyroglossal Duct Cystsmentioning
confidence: 99%
“…Como tiene un origen en la fase embrionaria puede dejar un festoneado sobre el hueso subyacente lo que suele indicar que requiere una extirpación más cuidadosa. Cuando se encuentran en otras localizaciones como la línea media cervical requieren el diagnóstico diferencial con otro tipo de lesiones como los quistes del conducto tirogloso y recientemente se ha descrito que la presencia de algunas características ecográficas como los septos, paredes irregulares y componente sólido en el interior sugiere un quiste tirogloso (6).…”
Section: Quistes Dermoidesunclassified